The Nexus : International Terrorism and Drug Trafficking from Afganistan - Shanty, Frank, 1950- (New Dehli Pentagon Press, 2012)
This book examines the specific issue of whether or not there is a nexus (link or point of convergence) between international opium and heroin trafficking and terrorist networks operating in or from Afghanistan. Since 9/11 many public officials and others have made definitive statements concerning an alleged nexus between criminal narcotics trafficking and terrorist networks in Afghanistan. Although some anecdotal and circumstantial evidence suggests that a linkage between drug traffickers and international terrorists may exist in Afghanistan, the question is whether a convincing case based on sound empirical data can be made regarding a nexus or linkage between Afghan-based terrorists and national or internationally-based drug traffickers.
Include Index and Bibliography
Keywords: Drug control -- Terrorism -- Afghanistan